CAN HORSE RIDING THERAPY HELP REDUCE EMOTIONAL AND BEHAVIOURAL PROBLEMS OF PUPILS WITH LEARNING DISABILITIES? (Proceedings of International Conference on Special Education, 2015)
This research was conducted to investigate if horse riding can help reduce behavioural and emotional problems of pupils with learning disability. The theories underlying the research is dynamic system theory , theory of neuronal group selection and sensory integration theory. Pupils with learning disabilities if put under programmes with animals can contribute to psychological, social and educational changes. Behaviour patterns can be chartered to increase a positive behavior. A convenient sampling of 5 pupils with learning disabilities from a secondary school in an integrated programme in Hulu Selangor were picked to be respondents. Qualitative research method, with non intervention observations, for horse riding, were administered for six weeks. The observations were triangulated by means of structured questions on teachers and parents. Manual coding was applied to analyse the observations. The analysis indicates that there were changes in the behavior of the children, children were happy and attempted to communicate with other people and able to interact better as compared to before they went for therapy. Parents and teachers too concluded that horse therapy can contribute to positive learning for pupils with learning disabilities.